Answer:
Step-by-step explanation:
We'll call the 2 numbers x and y. Starting with the last part of that first sentence "one number is 10 times the other number" can be written, in algebraic form:
y = 10x
Now on to the first statement about the numbers: "twice their sum" is 2(x + y) and "equals their product" is = xy. Putting that all together:
2(x + y) = xy and we know that y = 10x so
2(x + 10x) = x(10x) and
and
and
x(10x - 22) = 0 so
x = 0 or 10x - 22 = 0 which makes
x equal to ![\frac{22}{10}=2.2](https://tex.z-dn.net/?f=%5Cfrac%7B22%7D%7B10%7D%3D2.2)
So x = 2.2 and y = 22.
37 IS THE ANSWER IM NO YELLING LOL